Representation and exposition: being and walking along the designs of Boulevard 24 de Mayo in Quito, Ecuador (1991-2012) - Kléver Francisco Vásquez Vargas (ARQUISUR Revista, 2025)
The present study reflects on the last two urban-architectural proposals in Boulevard 24 de Mayo in Quito, Ecuador, which were developed in 1991 and 2012, respectively. We aim at identifying the conditions of being and walking along that urban space with historical presence. For this purpose, not only planimety and images of both interventions were used but also their development records and an interview with one of their authors. Their interpretation, which was based on comparing both projects including the relevant literature, brought out two design characteristics: representation and exposition, which are characterized by the differences between those that plan the city and those who live in it.